Heritage Tourism: The Role of Satisfaction as a Mediating Variable - Edy Purwanto; M. Munir Syam AR (Yayasan Sinergi Kawula Muda, 2025)
Sumenep is a city that has a rich history and culture that is very interesting to study. Of course, this wealth is one of the attractions of tourist destinations in Sumenep Regency. This research aims to determine the role of satisfaction in mediating the influence of tourist attraction and destination image on intention to visit again. This research was conducted in Sumenep Regency. The objects in this research are focused on palace and museum tourist destinations in Sumenep Regency. The sample used in the research was 190 respondents taken using the purposive sampling method. Data was obtained through distributing questionnaires to respondents. Hypothesis testing is carried out using multiple linear regression analysis and hierarchical regression analysis. This research found that attractiveness has a positive and significant influence on satisfaction and also the intention to visit again. The destination image variable also has a positive and significant influence on satisfaction and intention to visit again. Then, consumer satisfaction has a positive and significant influence on intention to revisit. Meanwhile, in the context of the role of satisfaction as a mediating variable, in this study it was found that satisfaction did not mediate the effect of attractiveness on intention to revisit. Meanwhile, satisfaction mediates the influence of the destination image variable on intention to revisit.